## Solve this equation: – 7x + 12 – 2x = 23 + 13x -7x+12-2x = 23+13% Step 1: Simplify by combining like terms that are on the

Solve this equation: – 7x + 12 – 2x = 23 + 13x

-7x+12-2x =

23+13%

Step 1: Simplify by combining like terms that are on the

same side of the equation. Which terms can be

combined? -7x and -2x

– 9x+12 =

-23

23+13x

-23

Step 2: Both sides of the equation contain a variable term. It

is possible to isolate the variable term on either the

left or right side of the equation. How would you like

to isolate the variable term?

-9x-11 =

+ 9x

+13x

+9x

-11 =

+ 22

+22x

= 22

Subtract 23

from both sides of the equation.

Step 3: Isolate the variable term on one side of the equation

by adding 9x to

both sides of the equation.

Correct Dividing both sides by 22

isolates x

## Answers ( )

Answer:subtract 23

Step-by-step explanation: